Anatomical Adaptation of Grey Mangrove (Avicennia marina) Leaf in the Pond and Coast Located in Mangunharjo, Semarang, Central Java - Atia Nadira Lumban Tobing; Sri Darmanti; Endah Dwi Hastuti; Munifatul Izzati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Mangrove is a brackish plant that can live in habitats with extreme environmental conditions. For instance, the grey mangrove (Avicennia marina) is a mangrove species that can adapt anatomically in habitats with a wide range of salinity, such as ponds and coasts. This study examines the forms of anatomical adaptation of A. marina by comparing the anatomical structure of A. marina leaves that live in two different habitats, namely pond, and coast in the Mangunharjo area, Semarang, Central Java. The third leaf from the tip of the tree branches was used as samples and taken from three different trees in each habitat. Cross-section prepared microscope slides of the leaves were made using the embedding method and observed using a photomicrograph. The quantitative data were analyzed using the T-test at a 90% confidence level, while the qualitative data were analyzed descriptively. The results showed that different environmental conditions do not cause differences in the anatomy of A. marina leaves, but there are some histological modifications as a form of adaptation. These modifications are differences in the thickness of the cuticle, adaxial epidermis, parenchymal palisade tissue, spongy parenchyma, and the number of xylem cells in one vascular bundle. This research might initiate more advanced studies regarding the correlation between mangroves’ anatomical structure and anatomical adaptation towards diverse environmental conditions. The results of this study are expected to provide information about the anatomical structure of A. marina leaves that live in two habitats with different environmental conditions.